Hubungan Penggunaan Tabir Surya dengan Derajat Akne Vulgaris pada Mahasiswa Fakultas Kedokteran Universitas Muhammadiyah Semarang - Farisa Salma Talitha; Eko Krisnarto; Kanti Ratnaningrum (Pusat riset dan Inovasi Nasional, 2025)
Acne vulgaris is a common form of inflammation that affects the polysebaceous unit, and is common among young adults and adolescents. Acne vulgaris is characterized by the presence of papules, comedones, nodules and pustules. This study aims to examine the relationship between sunscreen use and the severity of acne vulgaris in medical faculty students at Muhammadiyah University, Semarang. This study used a cross-sectional design. The sample in this study were students from the medical faculty at Muhammadiyah University, Semarang, who were included in the inclusion criteria. This research data was taken through a questionnaire distributed via zoom meeting. Data analysis in this study used the Spearman Rank test. The results of the analysis, it was found that there was a relationship between the use of sunscreen and the degree of acne vulgaris in medical faculty students at Muhammadiyah University, Semarang. (p = 0.041).